Strategia alokacyjna i strategia systemowa w rozwoju gospodarczym PRL - Wilczyński, Wacław (Wydział Prawa i Administracji UAM, 1987)
In the '80, Polish economy has reached structural and system deadlock. The above makes it impossible to utilize and to shape in the best possible manner the production potential. The main cause of that impasse has been a long-lasting adherence to the uniformism of the system and the rejection of attempts to introduce changes in that field over the last 30 years. An underestimated aspect of a centralized system is its influence on the consolidation of antiquated material structures and on the absence of demand for innovations. The article contains an attempt to estimate the system and allocation policies in the last 40 years; it points out to hampering influences of the system in the '60 and to the discrepancy between the developmental ambitions and an obsolete system in the '70. The factors determining the allocation and system strategy of the nearest years are developmental challenges of the end of the XXc and the present condition of the economy. Its present state requires an unreserved priority for a deep system reform, able to change hitherto existing economic relations and to overcome intertness. Only with the help of means obtained through the system changes will it be possible to carry out the programme of restructuring the economy. The economic policy of today must combine tough system decisions with the conscious shaping of the modern production potential.
The allocation strategy and the system strategy in the economic development of the Polish People's Republic